Analisis Sikap Konsumen dan Kinerja Atribut Sosis Kemasan Merek Fiesta di Wilayah Jabodetabek - Yunus, Zabrina; Suharno; Adhi, Andriyono Kilat; Suharno, Suharno (Jurnal Agribisnis Indonesia, 2025)
The intense competition in the packaged sausage industry necessitates that producers understand the attributes deemed important by consumers. Such understanding is crucial for formulating effective marketing strategies. This study has three primary objectives: to identify the consumer decision-making process in purchasing packaged sausages, to analyze consumer attitudes toward the product, and to evaluate the performance of various attributes of Fiesta brand packaged sausages. The findings of this study are expected to serve as an evaluation tool for companies in improving and developing products that better align with consumer preferences.This study employs a primary data approach, with data collected through a survey of 156 respondents. The data were analyzed using descriptive analysis, the multi-attribute Fishbein model, and Importance-Performance Analysis (IPA). The results indicate that consumers go through five stages in the decision-making process, ranging from need recognition to post-purchase behavior. Furthermore, consumer attitudes toward all attributes of Fiesta brand packaged sausages fall into the positive and highly positive categories, with the highest attitude score recorded for the clarity of the expiration date. The Importance-Performance Analysis (IPA) further reveals that the attributes of Fiesta brand packaged sausages are distributed across four quadrants of the Cartesian diagram. Among these attributes, variations in size/packaging options, sausage texture, and price have been identified as top priorities for improvement. Therefore, companies need to enhance or refine attributes that have yet to meet consumer expectations based on priority scales, ensuring a significant impact on consumers’ overall evaluation of the product.